1985
DOI: 10.1149/1.2114166
|View full text |Cite
|
Sign up to set email alerts
|

Crystalline Anodic Oxide Growth on Aluminum Foil in an Aqueous Ammonium Dihydrogen Phosphate Anodization Electrolyte

Abstract: The parameters affecting the growth of small crystallites within the anodic oxide film formed on aluminum during anodization in an 85°C aqueous ammonium dihydrogen phosphate electrolyte have been investigated. The degree of crystallinity of the anodic oxide was observed to increase with decreasing anodization current density and increasing voltage. The more crystalline films had a higher capacitance, were thinner, and contained less phosphorus than largely amorphous films anodized to the same voltage. A short … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 16 publications
1
14
0
Order By: Relevance
“…It has been reported that the thermally formed crystalline ␥-Al 2 O 3 could act as the nucleation site for forming ␥Ј-Al 2 O 3 in Al anodizing. 10,11 The presence of the outer layer of crystalline ␥Ј-Al 2 O 3 , as revealed in Fig. 2a, was probably associated with the thermal oxide formed during pre-heat-treatment.…”
Section: Resultsmentioning
confidence: 95%
“…It has been reported that the thermally formed crystalline ␥-Al 2 O 3 could act as the nucleation site for forming ␥Ј-Al 2 O 3 in Al anodizing. 10,11 The presence of the outer layer of crystalline ␥Ј-Al 2 O 3 , as revealed in Fig. 2a, was probably associated with the thermal oxide formed during pre-heat-treatment.…”
Section: Resultsmentioning
confidence: 95%
“…This scenario satisfies the conditions of thermodynamic equilibrium of different species on the Pourbaix diagram. However, the proposed scenario does not follow a scenario of anodic electropolishing of metals 35 37 38 39 which does not take into account thermodynamic constrains. These constrains are set on by the Pourbaix diagrams.…”
Section: Discussionmentioning
confidence: 99%
“…These constrains are set on by the Pourbaix diagrams. To the best of our knowledge, while the two-layer model has been sugested for almost half a century ago, the current literature dealing with electropolishing does not address the thermodynamic limitations associated with incorporation of electrolyte anions such as groups into the oxide structure 35 37 38 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Since the oxide obtained by anodic oxidation consists of -alumina, which can be only partially transformed in -alumina by heating to 6003C (Chen & Hutchins, 1985) this method cannot be applied for the present study. Therefore, a washcoating method was developed to deposit the needed -Al O layer in the microchannels of the stainless-steel reactor.…”
Section: Catalytic Coatingmentioning
confidence: 99%